CASE REPORT: PRIMARY HYPERPARATHYROIDISM AND JAW TUMOUR SYNDROME WITH CDC73 GENE MUTATION IN A YOUNG PATIENT - Peng, Sun Choon; Velaiutham, Shanty A/P (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Primary hyperparathyroidism (pHPT) occurs frequently in those over the age of 50 years. This condition is uncommon in young adults and are more likely to have an underlying germline mutation. CASE We present a case of a healthy 16-year-old male who was incidentally found to have an elevated calcium of 3.16 mmol/L. Family history revealed that his father, aunty and grandfather also had a history of hypercalcemia. No genetic study was done previously. The patient was diagnosed with iPTH-mediated hyperparathyroidism based on blood investigations. Localization scan revealed an overactive right parathyroid gland secreting excess iPTH. Subsequently, he was scheduled for right parathyroidectomy. Histopathology report confirmed the diagnosis of a right superior parathyroid adenoma. His iPTH level declined from 968.5 pg/ml to 7.9 pg/ml after the surgery while calcium and ALP levels also normalized. He subsequently required calcium and activated Vitamin D supplementation. The patient and his family were referred for further genetic assessment, revealing CDC73-related disorders, with a pathogenic mutation on CDC73 gene. The patient’s father was found to develop a jaw tumour with histologic confirmation of invasive ossifying fibroma. Hence, tumour debulking was planned. CDC73-related disorder is an autosomal dominant disorder resulting from the inactivation of the CDC73 tumor suppressor gene. The spectrum includes: Hyperparathyroidism jaw tumor (HPT-JT) syndrome, parathyroid carcinoma and familial isolated hyperparathyroidism (FIHP). Penetration of pHPT is as high as 80% to 95%, while parathyroid carcinoma may be found in more than 20% of patients. Lifelong surveillance is indicated for positive gene carriers to look for recurrent hyperparathyroidism, parathyroid carcinoma, renal and uterine tumour in females. CONCLUSION This case report demonstrated the importance of early detection of hypercalcaemia in a younger population, the need to obtain a comprehensive family history and the significance of proceeding with early germline CDC73 mutation detection for optimal clinical management of pHPT. Genetic counselling and surveillance of family members who are at risk of developing CDC73-related disorders must also be emphasized.